PENGARUH PERSEPSI KUALITAS PELAYANAN DAN BAGI HASIL TERHADAP MINAT MASYARAKAT MENJADI NASABAH BANK SYARI’AH - Sri Wahyuni (Universitas Islam Negeri Sumatera Utara, 2017)
Perception of the system for the results is the public perception that the system for these results more in line with the principles of Shari'ah.The approach in this study was the quantitative. The population in this research is the community around the working area of Bank Syari’ah Mandiri KCP Medan Simpang Limun as much as 242 family heads and samples acquired 97 respondents.Data analysis technique used is multiple regression. The results of the research there were obtained: the influence of quality of service (0.000); for the results (p = 0,016) against interest became Bank's Shariah; There is the influence of the quality of service and for the results against the interest became Bank's Shariah (p = 0.000). The better the quality of service and products that Shariah Bank given understandable public can cause a good perception that ultimately can lead to an interest in one's self into a bank's Shariah.